Pengaruh Gaya Kepemimpinan Terhadap Perilaku Kerja yang Inovatif - Mohammad Fanani; Endang Lifchatullaillah; Lailatus Sa’diah (Jurnal Simki Economic, 2023)
Leadership is one description of an institution as a process of influencing other people in a certain scope to work together in a productive way and in pleasant conditions. As a leader, you should be able to create a working atmosphere that creates a new and innovative atmosphere for your staff in achieving goals to be better and to obtain higher results than before. This study aims to analyze the Influence of Leadership Style on Innovative Work Behavior. The research design used is quantitative. The sample in this study was taken by probability/random with cluster random sampling technique. The analysis was carried out using univariate and bivariate methods. The results showed that training has a positive effect on employee performance and leadership style has a positive effect on employee performance.